Characterization of house and cave bird's nest in Malaysia and optimization of a bird's nest-based gel-like ready-to-drink product - Yap, Kim Chung (2020)
Edible bird’s nest (EBN) from the saliva of swiftlets has been esteemed as a precious food tonic because it possesses antiaging, anticancer, and immunity-enhancing properties. This study was conducted to characterize and determine the physicochemical properties of edible bird’s nest from cave nest and house nest (from genus Aerodramus) in Malaysia and develop EBN (gel-like) ready-to-drink formulation using RSM. All EBN samples used in this study were genuine raw samples collected from cave and house farm in Malaysia. Expansion rate study and SEM observations were performed to determine the different types and location factors that affect the physical profile of EBN. For chemical profile study, HPLC and HPAEC-PAD method was used to determine amino acid and glycoprotein profile. Based on the expansion and SEM observation, house nest samples have a better expansion rate and result indicated that the simpler (crystal-like) micromorphology of house nests has more surface area to absorb water in comparison to cave nest. Results from the amino acid analysis revealed that EBNs in Malaysia had very similar profiles. Leucine (39.65 – 41.88 mg/g), threonine (40.68 – 41.35 mg/g), and valine (37.90 – 40.44 mg/g) were the three major essential amino acids in both types of samples. There were no significant differences (P> 0.05) between the amino acid profiles of house EBN and cave EBN. Through glycoprotein analysis, N-acetylneuraminic acid/N-acetyl-D-galactosamine (Neu/GalN) ratio can be used as a benchmark to identify the quality of EBN. EBN from Kuantan ranked the highest quality among all the samples, with a Neu/GalN ratio of 5.28, while EBN from Parit Buntar ranked the lowest, with a reading of 2.01. The Neu/GalN ratio showed that the quality of EBN from Malaysia is equivalent to or better than EBN from Thailand, Indonesia, and Vietnam. Response surface methodology (RSM) was utilized to investigate the influence of the purified EBN (1–3%) and xanthan gum (0.5-1.5%), as well as the preparation temperature (25-75°C), on the gel strength, adhesiveness, and viscosity. The formulation and optimization of three independent variables were carried out to obtain an optimum EBN-based ready-to-drink product. The optimal bird’s nest (gel-like) ready-to-drink formulation was prepared with 3.00% EBN and 0.97% xanthan gum at 60°C. Currently, the gel-like EBN ready-to-drink products are not common in the market and this product can be used to penetrate new continents and not only relying on exporting raw EBN to China market.